Study on the Fingerprints and Quality Evaluation of Angelica Sinensis Radix by HPLC Coupled With Chemometrics Based on Traditional Decoction Process of ACPTCM. Issue 3 (21st September 2020) - Qian, Zhang; Yiyang, Chen; Lixia, Ma; Yue, Jiang; Jun, Chen; Jie, Dong; Yifan, Ma; Jingjing, Zhang; Guojun, Yan
Objective: To establish a HPLC fingerprints evaluation method for Angelica Sinensis Radix (ASR) based on traditional decoction process of Ancient Classical Prescriptions of Traditional Chinese Medicine (ACPTCM). Methods: The fingerprints of 10 batches of ASR were further evaluated by chemometrics methods. The similarity analyzed with "Similarity Evaluation System for Chromatographic Fingerprint of Traditional Chinese Medicine 2004A, " and hierarchical clustering analysis (HCA) and principal component analysis (PCA) were performed by SPSS (version 22.0, SPSS Inc., Chicago, IL, USA). Results: There were 12 common peaks, and the similarity degrees of 10 batches of samples were more than 0.923 and showed that all the samples from different origins were of good consistency. The samples were divided into 4 clusters by HCA. The results of PCA showed that the 3 factors were chosen, the quality of samples could be evaluated basically. The comprehensive score results show that the ASR with Lot.Nos.DG-18007, DG-18008 in Weiyuan County, Gansu and DG-18009 produced in Minle County, Gansu Province rank among the top 3 in all samples. Conclusions: These results demonstrated that the combination of HPLC chromatographic fingerprint and chemometrics offers an efficient and reliable approach for quality evaluation of ASR from different sources as Ancient Classical Prescriptions ingredients.